Interpersonal communication among parents and children in fishermen village in Cirebon Indonesia - Triwardhani, Ike Junita; Chaerowati, Dede Lilis (Penerbit Universiti Kebangsaan Malaysia, 2019)
Communication is crucial for the fishermen community in Indonesia because most of Indonesia's territory is the ocean. Being a fisherman was one of the backbone professions, and interpersonal communication was a bridge to inherit the traditional values of fishermen who had been passed down from their parents to their children from generation to generation. With communication, the local cultural values of the fishing community would be maintained. This paper discusses interpersonal communication in the basis of Attraction Theory and Theory of Relationship Stage. The writing was reviewed qualitatively using an ethnographic communication approach in fishermen community in Cirebon area of West Java. The study was based on direct observation of fishermen community activities, in-depth interviews, and focus group discussions with community in Citemu Village. The results of the study revealed that fishermen's work was done traditionally by making wadong, as well as selling and processing sea product. These activities were communicated by parents to children to inherit the local entrepreneurial value of fishermen. Parental interpersonal communication to children was carried out on the basis of attractions through creating meaning for the similarity of family background, physical and emotional closeness, giving rewards, and involving children in various fishing activities. Parents also paid attention to children's interest in being involved in activities, even economic pressure sometimes made parents use their authority. However, togetherness and the relationship between parents and children were conducted continuously, especially when problems occured because parents still believed that the closeness and blood bonding would restore and improve the relationship.